#TITLE_ALTERNATIVE# - SIHOTANG (NIM 12104048), ALVENSIUS
Block caving method in underground mining which is executed by DOZ PTFI will result on existence of a huge cave for ore collapse process. This matter results in existed in situ stress will be distributed to those areas which have intact rocks around the caving boundary. The accumulation of stress will be existed in those areas. This increase of stress will disturbing the cave stability around the area. Research which was performed by R. Trueman et al. (2002) and Rachmad & Widijanto (2002) stated that initial stress will be distributed and accumulated around the collapse boundary. Another research which was performed by Rachmad & Widijanto (2002), RK Wattimena et al. (2006) and some experiences in PTFI that revealed that convergence monitoring can provide a similar trend and information regarding stress having been around the extraction level just like another more complex stress monitoring. The analysis of relationship between convergence and observation distance around caving boundary indicate that the convergence value will be greater if the observation is closer to caving boundary. The analysis of damage condition toward convergence changes indicates increasing of damage class when the increase of convergence rate exceeds the limit of convergence rate. Meanwhile some cases indicate the changes of damage class occur when the continuously increase of cumulative convergence is existed despite of the normal convergence rate. The calculation of cave stability which is based on average convergence rate is performed by splitting the observation time into periods based on data dissemination on graph. From this analysis, we can conclude that the condition is stable in almost all observation station area except for station 03 panel 1B for 3 June 2008-15 July 2008 period. Meanwhile, the determination of period for stability analysis based on damage condition starts from the timing of damage mapping. This analysis indicates the stable condition in all measurement station, yet the anticipation action is still necessary in several locations on panel 1B, they are station 03, 04, 07, and 09, due to the occurrence of 3rd class of damage condition. With reason if the damage approaches the 4th class of damage or partial closure of drift until half of initial broad of tunnel occur , this condition will cause instable condition and the production ceases.